The study of challenges faced by property management in managing the high rise apartment in Genting Highlands - Nor Azmi, Annas (Universiti Teknologi MARA (UiTM), 2025)
The management of high-rise apartments in Genting Highlands presents unique challenges due to its high-altitude environment, harsh weather, and growing infrastructure demands. This study investigates the multifaceted challenge faced by property managers, including structural maintenance, tenant relations, and regulatory compliance, with a focus on preventive, predictive, and corrective maintenance strategies. Using a qualitative approach, the research draws insights from property managers of four residential properties: Ria Apartment, Vista Residence, Ramin Apartment, and RSC Apartment. Data collected through structured interviews and NVivo analysis revealed recurring challenges such as water seepage, elevator malfunctions, HVAC failures, and tenant cooperation. Technology and predictive tools have emerged as critical components in addressing these challenge, enabling proactive and efficient maintenance practices. Findings highlight the importance of strategic budgeting, advanced training, and effective communication in overcoming obstacles. Weather-related damage, aging infrastructure, and resource constraints remain persistent challenge, requiring innovative solutions and stakeholder collaboration. This study offers actionable recommendations to enhance property management practices, contributing to the sustainability, safety, and efficiency of high-rise apartments in Genting Highlands and similar environments